Supramolecular Assembly of Human Pulmonary Surfactant Protein SP-D. Issue 10 (11th May 2018) - Arroyo, R.; Martín-González, A.; Echaide, M.; Jain, A.; Brondyk, W.H.; Rosenbaum, J.; Moreno-Herrero, F.; Pérez-Gil, J.
Abstract: Pulmonary surfactant protein D (SP-D) is a glycoprotein from the collectin family that is a component of the lung surfactant system. It exhibits host defense and immune regulatory functions in addition to contributing to the homeostasis of the surfactant pool within the alveolar airspaces. It is known that the SP-D monomer forms trimers, which further associate into higher-order oligomers. However, the pathway and the interactions involved in the assembly of SP-D oligomers are not clearly understood. In the current study, a recombinant form of full-length human SP-D (rhSP-D) has been qualitatively and quantitatively studied by atomic force microscopy (AFM) and electrophoresis, with the aim to understand the conformational diversity and the determinants defining the oligomerization of the protein. The rhSP-D preparation studied is a mixture of trimers, hexamers, dodecamers and higher-order oligomeric species, with dodecamers accounting for more than 50% of the protein by mass. Similar structures were also found in hSP-D obtained from proteinosis patients, with the largest fuzzy-ball-like oligomers being more abundant in these samples. The proportion of dodecamer is increased under acidic conditions, accompanied by a conformational change into more compact configurations. Two hexamers appear to be the minimal necessary unit for dodecamer formation, with stabilization of the dodecamer occurring via non-covalent, ionic, and hydrophobic interactions between the individual N-terminal domains and the proximal area of the SP-D collagen stems. Graphical Abstract: Highlights: rhSP-D and hSP-D are found as trimers, hexamers, dodecamers and larger oligomers. Dodecamers are the most abundant oligomer of the protein. Hexamers play an important role in the oligomerization of SP-D. Non-covalent interactions are important to form and maintain dodecamers and larger oligomers. Distribution and 3D conformation of the oligomers is sensitive to environmental conditions such as pH.